2001
DOI: 10.1007/s001340101021
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive radiation-free monitoring of regional lung ventilation in critically ill infants

Abstract: Provided that EIT hardware and software are further developed to guarantee stable and undisturbed measurements in the ICU and that practical handling is improved, this non-invasive method may become a useful bedside monitoring tool of regional lung ventilation in critically ill infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
17

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 23 publications
1
51
0
17
Order By: Relevance
“…It might be that the lung behaves different to positional change in the first hours after extubation to nCPAP. A previous report in a term born infant seems to support this hypothesis as ventilation distribution clearly shifted to the ventral region after placing this infant in prone position 1 h after extubation (15). Whether this shift in ventilation distribution to the ventral lung regions is consistent over time cannot be answered by this study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…It might be that the lung behaves different to positional change in the first hours after extubation to nCPAP. A previous report in a term born infant seems to support this hypothesis as ventilation distribution clearly shifted to the ventral region after placing this infant in prone position 1 h after extubation (15). Whether this shift in ventilation distribution to the ventral lung regions is consistent over time cannot be answered by this study.…”
Section: Discussionmentioning
confidence: 46%
“…Furthermore, EIT also provides information on regional changes in volume and ventilation (12)(13)(14). Recent studies have shown that EIT is feasible in the preterm population and that the lung volume changes measures in the examined slice are representative for the whole lung (15)(16)(17).…”
mentioning
confidence: 99%
“…We did, however, find a significantly higher increase in Vosc in the right lung compared with the left lung. This right-sided predominance is probably best explained by the presence of the heart in the left hemithorax [21,26].…”
Section: Discussionmentioning
confidence: 99%
“…EIT has already been used to study adult [37,[42][43][44] and paediatric ARDS patients [27] as well neonatal patients suffering from respiratory distress syndrome [45,46]. The number of studied patients was rather low and EIT data were usually acquired only during short time intervals.…”
Section: The Value Of Eit In Monitoring Patients With Ardsmentioning
confidence: 99%
“…Although EIT monitoring lasting for several hours or days has been described in case reports [46] no long-term clinical studies using EIT have ever been performed. The reproducibility of EIT findings has also been documented only over rather short time intervals [68].…”
Section: The Limitations Of Eitmentioning
confidence: 99%